Tiny encryption algorithm and pixel value differencing for enhancement security message - Rahim, Robbi; Adyaraka, Danadyaksa; Sallu, Sulfikar; Sarimanah, Eri; Mihram Rahman, Muhammad; L. Chusna, Nuke; Hartinah, Sitti; Kusuma Astuti, Endang; Kurniasih, Nuning (International Journal of Engineering and Technology, 2018)
A combination of algorithms to improve text security is possible, Tiny Encryption Algorithm and Pixel Value Differencing are two possible combinations of algorithms. Cryptography and steganography processes can be done to secure messages with two stages, encryption for the first stage and the second one for steganography. Using this two-stage make it difficult for irresponsible parties to know information.Â Â